Economic burden of chemotherapy-treated recurrent and/or metastatic squamous cell carcinoma of the head and neck in France: real-world data from the permanent sample of national health insurance beneficiaries. (3rd July 2019) - Lafuma, Antoine; Cotté, François-Emery; Le Tourneau, Christophe; Emery, Corinne; Gaudin, Anne-Françoise; Torreton, Elodie; Gourmelen, Julie; Bonastre, Julia
Abstract: Aims: Overall survival (OS) of patients with recurrent or metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN) is extremely poor. New therapeutic options emerge but need to establish their economic value. The objective was to describe the direct and related costs of R/M SCCHN in France. Materials and methods: We selected all adult patients treated with chemotherapy for R/M SCCHN between 1 January 2009 and 31 December 2014 from the permanent sample of the French national health insurance database (EGB). Data were analyzed from the index date (first chemotherapy) until patients' death or 31 December 2015. "Treatment period" and "end-of-life" (EoL) (from last chemotherapy until death) were distinguished. Costs included all hospitalizations for SCCHN and ambulatory care. Costs of hospitalized and non-hospitalized adverse events (AEs) were estimated. Results: Among 267 patients identified, 85% were men, 44% had metastases at the index date and the mean age was 62.0 years (±9.9). The most common tumor location was oropharynx (29%) but 39% of patients had multiple locations. Median OS was 9.3 (95% CI: 7.9–11.8) months for the overall population. The average total direct cost per patient was €49, 954, broken down into €32, 908 (95% CI: 29, 525–36, 290) for hospitalizations and €17, 047 (14, 941–19, 152) for ambulatory care. Main cost drivers were drug acquisition and administration (€14, 538) during the treatment period (209 days on average) and palliative care (€3, 750) during the EoL period (125 days). Regarding related costs, around 12% of patients received disability pensions (€1, 397 per patient [624–2, 171]) and sick leave payments (€1, 592 [888–2, 297]). "Metabolism and nutrition disorders" and "Infections and infestations" were the most expensive hospitalized AEs (€1, 513 and €1, 180 per patient, respectively). Febrile neutropenia was the most expensive non-hospitalized AE (€766 per patient). Conclusions: This analysis of real-world data confirms the poor prognosis of patients with R/M SCCHN and provides cost data for future economic evaluations.